1997
DOI: 10.1002/(sici)1097-0231(199703)11:5<504::aid-rcm886>3.0.co;2-5
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Ceramides in Human Cells Using Liquid Chromatography with detection by Atmospheric Pressure Chemical Ionization-Mass Spectrometry

Abstract: Ceramides are intermediates in the biosynthesis of membrane sphingolipids. These biomolecules are also important as second messengers in signal transduction pathways controlling cell growth. We have developed two reversed-phase high pressure liquid chromatography (RPHPLC) techniques for identification and quantification of ceramides from mammalian cells. One method was based on atmospheric pressure chemical ionization-mass spectrometry (APCI-MS) detection of ceramides and had the advantage of requiring minimal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2000
2000
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(18 citation statements)
references
References 20 publications
1
17
0
Order By: Relevance
“…Ceramides, which are nonphosphate-containing interme- diates in the biosynthesis of sphingolipids, were analyzed by Couch et al (55) using HPLC with detection by APCI-MS. They reported the analysis of both underivatized and perbenzoylated ceramide standards and ceramides from human leukemic cells using detection by APCI-MS and UV-Vis.…”
Section: Phospholipidsmentioning
confidence: 99%
“…Ceramides, which are nonphosphate-containing interme- diates in the biosynthesis of sphingolipids, were analyzed by Couch et al (55) using HPLC with detection by APCI-MS. They reported the analysis of both underivatized and perbenzoylated ceramide standards and ceramides from human leukemic cells using detection by APCI-MS and UV-Vis.…”
Section: Phospholipidsmentioning
confidence: 99%
“…Determine optimal collision energy for each subspecies in each class (such as C 12 Cer, C 16 Cer, C 18 Cer, C 20 Cer, C 22 Cer, and C 24 Cer), including the internal standards. …”
Section: Identify Specific Sphingolipid Precursor and Product Ion Paimentioning
confidence: 99%
“…Other methods for the analysis of sphingolipids by mass spectrometry have been described (12,(14)(15)(16)(17)(18)(19). Besides mass spectrometry, a common method for the analysis of ceramide is to use Escherichia coli diglyceride kinase to produce a radiolabeled derivative (20), which must be done under carefully controlled conditions to be accurate (21).…”
Section: Related Techniquesmentioning
confidence: 99%
“…While many conventional methods, such as gas chromatography-mass spectrometry (MS) [15], thinlayer chromatography (TLC) [16], diacylglycerol (DAG) kinase assay [17], liquid chromatography (LC)-evaporative light-scattering detection [18] and LC-UV detection using a derivatizing technique [19], have been used to determine CERs, Mano et al [20], Gu et al [21] and Couch et al [22] reported MS using electrospray ionization (ESI) or atmospheric pressure chemical ionization (APCI) to be a valuable tool in the analysis of mixed CERs in 1997. Since the methods based on ESI-MS or APCI-MS were far superior to the conventional methods in terms of sensitivity and selectivity, since after their articles, many methods using LC-MS and tandem MS (MS/MS) for the analysis of CERs have been developed.…”
Section: Introductionmentioning
confidence: 99%